Preparation and Corrosion Inhibiting Mechanism of Bio-based Cerium Phytate Nanoparticles - Arnold, Steve C.; Domegan, Dmitry (Journal of Green Energy and Environmental Engineering, 2026)
Bio-based cerium phytate (Ce-PA) was synthesized using phytic acid (PA) and cerium nitrate. Subsequently, a series of epoxy coatings with varying Ce-PA contents (based on the mass of epoxy resin) were prepared. Ce-PA was characterized by FTIR, TGA, and SEM. The microstructural characteristics, mechanical performance, and corrosion protection efficacy of the coatings were systematically assessed, and the protective mechanism of Ce-PA within the epoxy matrix was elucidated. The results indicated that Ce-PA possessed an average particle size of 185 nm, demonstrating good monodispersity and thermal stability. Furthermore, Ce-PA exhibited excellent dispersibility within the epoxy matrix and endowed the coatings with favorable mechanical properties. The Ce-PA leachate effectively protected aluminum alloy from corrosive media, achieving a protection efficiency of 98.7%. Specifically, the coating formulation incorporating 4% Ce-PA preserved a coating resistance of 1.0×10⁸ Ω·cm² following 50 days of immersion in 3.5 wt% NaCl solution. Even for coatings with artificial defects, the resistance remained at 7.5×10⁶ Ω·cm² after 14 days of exposure. In aqueous environments, Ce-PA released Ce⁴⁺ and PAⁿ⁻ ions, which collectively formed a composite protective layer comprising a phytic acid conversion coating and Ce(OH)₄ deposits on the aluminum substrate, thereby markedly improving the corrosion resistance of the epoxy coating system.